95.9k views
0 votes
Solve for x: 3(x + 1) = −2(x − 1) − 4. (1 point)

a
1

b
−1

c
−5

d
−25

User Nate Raw
by
4.9k points

2 Answers

7 votes

Answer:

B. -1

Explanation:

short answer

User Alejandro De Haro
by
5.1k points
6 votes

3(x + 1) = −2(x − 1) − 4

Multiply the first bracket by 3

(3)(x)=3x

(3)(1)=3

Multiply the second bracket by -2

(-2)(x)=-2x

(-2)(-1)=2

3x+3=-2x+2-4

3x+3=-2x-2

Move -2x to the other side. Sign changes from -2x to +2x.

3x+2x+3=-2x-2x-2

3x+2x+3=-2

5x+3=-2

Move +3 to the other side. Sign changes from +3 to -3.

5x+3-3=-2-3

5x=-5

Divide by 5 for both sides

5x/5=-5/5

x=-1

Answer: b. -1

User Bestter
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.